Sunlit Riffles and Shadowed Runs : Stories of Fly Fishing in America - Cowgill, Kent (Book collections on Project MUSE., 2012)
Ranging from the comic to the nostalgic, edgy, and suspenseful, these short stories offer engaging portraits of characters across the spectrum of life, all absorbed by the thrill of fly fishing. A marriage betrayal on a trout stream in the north woods; angler rage on the redfish flats of the Gulf of Mexico; the intensity of combat fishing on a salmon pool in the Pacific Northwest - all rendered in sparkling prose that will resonate with anglers, and delight readers who enjoys outdoor pastimes.